UPAYA MENURUNKAN PREVALENSI DEMENSIA MEALUI EDUKASI KESEHATAN TERKAIT FAKTOR RESIKO DEMENSIA DAN DETEKSI DINI GANGGUAN KOGNITIF PADA POPULASI LANSIA DI MASYARAKAT PESISIR LOMBOK - Saputri, Legis Ocktaviana; Rivarti, Arina Windri; Harahap, Herpan Syafii; Nurhidayati, Nurhidayati; Suryani, Dini; Stephen, Mishael Enoch; Prawiro, Aurellia Wongso; Wulandari, Inayah; muttaqin, Syihabul; Ristia, Ovia Intan; Azizaturrahmah, Gina Aulia; Balqis, Ananda Amirah (Universitas Mataram, 2024)
Dementia is a progressive disease that affects memory and other cognitive functions. Coastal communities have a higher incidence of certain diseases compared to other areas. Degenerative diseases such as coronary heart disease, stroke, hypertension, diabetes mellitus, and dementia have an incidence rate of two to eight percent higher in coastal areas. This community engagement aims to provide health education related to the signs and symptoms as well as prevention efforts for degenerative diseases and cognitive function disorders. Health screenings are also conducted in an effort to detect cases of degenerative diseases and cognitive function disorders early. The community service activities are carried out in three coastal areas of Lombok Island. Participants enthusiastically attend health education and health screening. The results of cognitive function disorder screening show that 50.7% of the 225 participants experience cognitive function disorders. The community service activities are conducted according to plan.